Selective Conversion Of Methane To C2 Hydrocarbons Using Carbon Dioxide As An Oxidant Over Cao-Mno/Ceo2 Catalyst - Amin, Nor Aishah Saidina; Istadi, Istadi (Elsevier B.V., 2006)
Carbon dioxide rather than oxygen seemed to be an alternative oxidant for the catalytic reaction of methane to produce C2 hydrocarbons via oxidative coupling of methane (CO2 OCM). The proper amount of medium and strong basic sites and the reducibility of the catalyst enhanced the C2 hydrocarbon selectivity and yield, which may be due to the synergistic effect of CeO2, CaO and MnO in the catalyst. The C2 hydrocarbons selectivity and yield of 75.6% and 3.9%, respectively were achieved over 12.8CaO-6.4MnO/CeO2 catalyst. The catalyst showed a high stability for 20 h time on stream in the CO2 OCM process.